Pengelolaan Barang Milik Negara Melalui Kompetensi Sumber Daya Manusia dan Pengendalian Intern - Masruhati, Ta'ti (Universitas Prof. Dr. Moestopo (Beragama), 2025)
The study was conducted with the aim of determining the effect of human resource competence and internal control systems on State Property management with the use of information technology as a moderating variable at the Judicial Commission. This study uses a quantitative approach. The population in this study were 50 Judicial Commission employees related to BMN management. The sampling technique in this study used non-probability sampling. The sampling period started in July 2024 - August 2024. The data analysis method in this study used multiple regression model analysis with panel data and interaction tests or commonly called moderated regression analysis. The results of this study indicate that Human Resource Competence has an effect on State Property Management. The Internal Control System has an effect on State Property Management. The use of Information Technology can moderate Human Resource Competence in State Property Management. The use of Information Technology cannot moderate the Internal Control System in State Property Management.